2018
DOI: 10.1111/cga.12312
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the CYP1B1 gene in Pakistani primary congenital glaucoma patients: Identification of four known and a novel causative variant at the 3′ splice acceptor site of intron 2

Abstract: Funding informationQuaid-i-Azam University Primary congenital glaucoma (PCG) causes blindness in early age. It has an autosomal recessive pattern of inheritance, hence is more prevalent in populations with frequent consanguineous marriages that occur in the Pakistani population. Mutations in the CYP1B1 gene are commonly associated with PCG. The aim of the present study was to identify genetic mutations in the CYP1B1 gene in PCG cases belonging to 38 Pakistani families. DNA was extracted using blood samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
(114 reference statements)
1
8
0
1
Order By: Relevance
“…; p. Ser476Pro is 44% prevalent in India, p.Arg469Trp, p.Arg368His, p.Arg390His, p.Gly61Glu and p.Glu173Arg are 70% prevalent in Iran, p.Gly61Glu, p. Arg390His and p.Glu229Lys are [15]. Previous studies from Pakistan had reported p.Arg390His mutation to be implicated in more than 50% of analyzed PCG cases [6,20,38,39]; however, in present study, we did not identify this mutation in any of the analyzed case. A possible explanation of non-detection of p.Arg390His mutation in our study cohort could be the differences in ethnicities of analyzed subjects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; p. Ser476Pro is 44% prevalent in India, p.Arg469Trp, p.Arg368His, p.Arg390His, p.Gly61Glu and p.Glu173Arg are 70% prevalent in Iran, p.Gly61Glu, p. Arg390His and p.Glu229Lys are [15]. Previous studies from Pakistan had reported p.Arg390His mutation to be implicated in more than 50% of analyzed PCG cases [6,20,38,39]; however, in present study, we did not identify this mutation in any of the analyzed case. A possible explanation of non-detection of p.Arg390His mutation in our study cohort could be the differences in ethnicities of analyzed subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Up till now almost 270 mutations are reported in CYP1B1 gene including missense, small deletions, indels, gross deletions and regulatory mutations [19]. Studies have revealed several genetic mutations causing PCG from Pakistani population, but this data is still too limited as compared to high prevalence of this disorder in our population due to consanguinity [6,10,15,20]. In an ongoing effort of mutation screening of CYP1B1 gene in PCG cases belonging to consanguineous Pakistani families, we enrolled and screened twenty-five families for CYP1B1 variants.…”
Section: Introductionmentioning
confidence: 99%
“…Among enrolled cases 95% cases belonged to inbred families with 82.5% being products of first cousin unions ( Table 2 ). This observation is attributed to high degree of consanguinity, a main determinant of the high incidence of recessive disorders in our population [ 16 , 17 ]. Furthermore, 5% cases were not belonging to consanguineous parents which show presence of minor allele in general population with possibility of compound heterozygous variations predisposing to clinical manifestation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As FANCA is reported to be responsible for about 60%-70% cases of FA (SELENTI et al, 2015) and FA is inherited as autosomal recessive disorder. All autosomal recessive diseases are highly prevalent in inbred populations (FIRASAT et al, 2017;AFZAL et al, 2019) therefore Asian populations where consanguinity is customary have higher incidence FA. All the articles published till March, 2019 were assessed from www.ncbi.nlm.nih.gov/pubmed to extract data regarding mutations of FANCA gene including type of mutation, location of mutation, amino acid/protein change, population from where reported and study protocol.…”
Section: Fanca Mutations In Asian Populationmentioning
confidence: 99%